Periosteum-Derived Mesenchymal Stem Cells Secretome - Cell-Free Strategy for Endogenous Bone Regeneration: Proteomic Analysis in Vitro - Mindaugas Pranskunas; Egidijus Simoliunas; Milda Alksne; Algirdas Kaupinis; Gintaras Juodzbalys (Stilus Optimus, 2021)
Objectives: Millions of people worldwide are affected by diseases or injuries which lead to bone/tooth loss and defects. While such clinical situations are daily practice in most of the hospitals, the widely used treatment methods still have disadvantages. Therefore, this field of medicine is actively searching new tissue regeneration techniques, one of which could be stem cell secretome. Thus, the purpose of this research study was to perform the detail proteomic analysis of periosteum-derived mesenchymal stem cells secretome in order to evaluate if it is capable to induce osteo-regenerative process. Material and Methods: Periosteum-derived mesenchymal stem cells (PMSCs) were extracted from adult male New Zealand White rabbits. Cells were characterised by evaluating their differentiation potential. After characterisation PMSCs secretomes were collected and their proteomic analysis was performed. Results: PMSCs were extracted from adult male New Zealand White rabbits. In order to characterise the extracted PMSCs, they were differentiated in the directions which mainly describes MSC multipotency - osteogenic, myogenic and adipogenic. A total of 146 proteins were detected. After characterisation PMSCs secretomes were collected and their proteomic analysis was performed. The resulting protein composition indicates the ability to promote bone regeneration to fully mature bone. Conclusions: Bioactive molecules detected in periosteum-derived mesenchymal stem cells secretome initiates the processes required for the formation of a fully functional bone.